RETHINKING BITUMEN: FROM “BULLSHIT” TO A “MATTER OF CONCERN” (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
What is the current state of discourse about bitumen and how might it be changed? Philosopher Harry Frankfurt defines “bullshit” as any attempt at persuasion that is “unconnected to a concern with the truth” (Frankfurt). By looking at a variety of recent examples from the debates over bitumen extraction, “Rethinking Bitumen” argues that these debates have many of the characteristics that Frankfurt ascribes to “bullshit.” It is argued further that the debate’s disconnect from a concern with truth is rooted in what Bruno Latour calls “matters of fact” (“Critique” 226).  Attempts to persuade are built on “matters of fact”—which can be debunked by both sides as ideological—when they should be founded on the ecological consciousness of what Latour calls “matters of concern” (ibid.) Literature offers one means of effecting this transition from “matters of fact” to “matters of concern.” This article considers Marc Prescott’s play Fort Mac as one example of a literary text that creates an opportunity for engaging in ecological thinking about bitumen and for deploying affect and sensation to change the prevailing values about it, to see bitumen as a “matter of concern.”